Thermal Decomposition Enhancement of HMX by Bonding with TiO2 Nanoparticles. Issue 4 (29th January 2019) - Zhu, Qing; Xiao, Chun; Xie, Xiao; Zheng, Bao‐hui; Li, Shang‐bin; Luo, Guan
Abstract: The appropriate structure and properties of a composite material, including the morphology, particle size, and bond strength, are very important for its performance and practical applications. The energetic material HMX (C4 H8 N8 O8, cyclotetramethylenetetranitramine) is typically mixed with nanocatalysts to improve its thermal decomposition, which is advantageous for its detonation performance in practical applications. Inspired by the bioadhesion of mussels, a HMX@PDA@TiO2 (HMX first coated with PDA film and second coated with TiO2 nanoparticles) composite was developed in this study to greatly advance the thermal decomposition temperatures. A simple stirring process was used to prepare the composite from HMX and TiO2 nanoparticles under dopamine solutions with different pH values. Nanocatalyst TiO2 nanoparticles were anchored on the surface of HMX by reacting with the dopamine and polydopamine coatings. Compared with other reference samples, the thermal behavior of the obtained composite showed that the starting decomposition temperature was lower, at approximately 60 °C, and that the decomposition peak decreased by 35 °C, indicating that the composite properties should have great effects on the thermal performance of the materials. The findings offer a valuable composite preparation method to enhance the thermal behavior and the effect of the catalyst on the composite via bonding effects. Abstract :